Discussion of Psychological Factors Influencing the Development of Verbal and Communicative Competencies - Ismoilov T.I. (Periodica Journal, 2023)
This article conducts an extensive analysis of the psychological aspects that influence the development of verbal and communicative competencies in humans. The study is based on current theories and empirical research in the psychology of communication and language learning. The article examines the importance of psychological aspects such as motivation, self-esteem, emotional intelligence and social factors in the formation and development of verbal communication competence. The authors analyze in detail the relationship between the emotional state and the ability to express one's thoughts and ideas in words, and also consider the influence of motivation on the level of skill in the field of verbal communication. The article also raises the issue of the influence of the social environment and interpersonal relationships on the development of verbal skills, highlighting key aspects such as upbringing, patterns of behavior and the structure of society.
Keywords: Verbalcommunicative competencies; Psychological factors; Development of communication skills